PENGARUH PERSONAL BRANDING HABIB JA’FAR HUSEIN AL-HADAR TERHADAP MODERASI BERAGAMA MAHASISWA STAIN MAJENE MELALUI TERPAAN MEDIA SOSIAL TIKTOK - Rahim, Zulkifli; Aldiawan (Rumah Jurnal STAIN Majene, 2025)
This study aims to examine the influence of Habib Ja'far Husein Al-Hadar's personal branding on religious moderation among students at STAIN Majene through the exposure of TikTok social media. Habib Ja'far, a preacher known for his high level of tolerance, uses social media platforms, especially TikTok, to deliver religious messages in a light, casual, and easily understandable approach for various audiences. This research employs an explanatory survey method with a quantitative approach, where data was collected through questionnaires given to STAIN Majene students. The results indicate that Habib Ja'far's personal branding, recognized for his moderate preaching and emphasis on interfaith tolerance, significantly influences the improvement of religious moderation understanding among students. Furthermore, the use of TikTok as a medium for preaching has proven effective in reaching young audiences, especially students, with short video durations and content relevant to daily life. These findings demonstrate that strong personal branding and the proper use of social media can enhance the understanding of religious moderation, especially among the younger generation.